Synthesis of 2-(4-Isopropylthiazol-2-yl)-7-methoxy-8-methylquinolin-4-ol; A Quinoline Building Block for Simeprevir Synthesis - Rádl, Stanislav; Rezková, Hana; Obadalová, Iva; Srbek, Jan; Břicháč, Jiří; Pekárek, Tomáš (Synthesis, 2014)
Two synthetic approaches to the achiral quinoline fragment of simeprevir are described. Both approaches are based on the synthesis of methyl 4-hydroxy-7-methoxy-8-methylquinoline-2-carboxylate, protection of its 4-hydroxyl group, and construction of the thiazole ring from the ester group at the 2-position. The last step is acid deprotection of the 4-hydroxyl protecting group.
Keywords: antiviral agents; building block; quinolones; thionation; thiazoles